2023
DOI: 10.3389/fonc.2023.1174713
|View full text |Cite
|
Sign up to set email alerts
|

Microwave ablation induces abscopal effect via enhanced systemic antitumor immunity in colorectal cancer

Abstract: BackgroundThermal ablation is the primary procedure for the local treatment of lung metastases. It is known that radiotherapy and cryoablation can stimulate an abscopal effect, while the occurrence of abscopal effect induced by microwave ablation is less; the cellular and molecular mechanisms involved in the abscopal effect after microwave ablation should be further elucidated.MethodsCT26 tumor-bearing Balb/c mice were treated with microwave ablation with several combinations of ablation power and time duratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…Huang et al found that MWA alone failed to produce a significant abscopal effect, but the combination of MWA and immunotherapy resulted in the inhibition of distant tumor growth and reduced recurrence [27]. On the other hand, Yu reported that MWA not only suppressed tumor growth in the primary tumors but also stimulated an abscopal effect in CT26-bearing mice via the improvement of systemic and intratumoral antitumor immunity [42]. These studies implied that although MWA, like other ablative therapies, has an increase in interleukin-1 and heat shock proteins during cancer cell death via thermal injury, MWA is less inducible compared to radiofrequency ablation and cryoablation [35,43].…”
Section: Discussionmentioning
confidence: 99%
“…Huang et al found that MWA alone failed to produce a significant abscopal effect, but the combination of MWA and immunotherapy resulted in the inhibition of distant tumor growth and reduced recurrence [27]. On the other hand, Yu reported that MWA not only suppressed tumor growth in the primary tumors but also stimulated an abscopal effect in CT26-bearing mice via the improvement of systemic and intratumoral antitumor immunity [42]. These studies implied that although MWA, like other ablative therapies, has an increase in interleukin-1 and heat shock proteins during cancer cell death via thermal injury, MWA is less inducible compared to radiofrequency ablation and cryoablation [35,43].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, recent studies have highlighted the potential of thermal ablation to induce systemic anti-tumor immunity, exhibiting the abscopal effect in which the ablation of local tumors leads to the regression of distant untreated tumor sites (32)(33)(34)(35). Cite a case, a 69-year-old patient with metastatic lung squamous cell carcinoma underwent MWA of a lesion in the right lower lung after developing immunotherapy resistance.…”
Section: Impact Of Thermal Ablation On Immunitymentioning
confidence: 99%
“…Xu et al ( 15 ) reported spontaneous regression of distant tumor lesions after MWA in patients with lung metastasis of endometrial carcinoma. To the best of our knowledge, however, few cases of MWA-induced abscopal effects have been reported ( 16 ), and the specific mechanisms underlying the abscopal effects remain to be elucidated.…”
Section: Introductionmentioning
confidence: 99%